IMPORTANCE OF POSTUROLOGY AS PREVENTION AND INTERVENTION FOR MUSCULOSKELETAL AND SPINAL DEFORMITIES - Petya Kasnakova; Biyanka Tornyova; Tanya Paskaleva (Journal of IMAB)
Posturology is a modern science of correct posture, which deals with the diagnosis, dynamic observation and disorder in body posture. The consequences of incorrect posture often lead to musculoskeletal and spinal deformities. The purpose of the research is to understand the importance of post-typology for the prevention of spinal distortions and the preparation of a rehabilitation program for musculoskeletal deformities. Material and methods: We used a documentary method and an empirical study. The functional study was conducted in the period 2022-2024 on the territory of Plovdiv and Haskovo regions. 488 individuals between the ages of 18 and 65 were studied, 49.8% (n = 248) females and 49.2% (n = 240) males. The diagnosis was made with special tests for spinal dysfunctions. A survey was conducted on physical activity, poor posture and overweight. Statistical methods were applied to process the results. Results: A kinesiological analysis of musculoskeletal and spinal deformities was performed. Improper posture during functional stress of the musculoskeletal system is widespread among the respondents in 52.2%, and after excessive loading, they report previous phenomena such as pain in 45.1%, numbness, etc. The thesis of insufficient motor activity and the need for a kinesitherapy program consistent with the findings of the functional examination is confirmed. Conclusion: Posturology provides an opportunity for diagnosis, treatment and prevention of common joint and musculoskeletal injuries due to the interrelationships with other body systems. Correct human posture is one of the signs of good physical development and health.